PERCERAIAN DI KALANGAN BURUH MIGRAN DI BANJARSARI, NUSAWUNGU, CILACAP - Al Anshor, Muchimah (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
Family economy is one of the supporting factors in making household harmony. Various ways are taken by the couple of husband and wife to increase the family economy. One of the ways is working abroad or becoming migrant workers. The majority of husband or wife in Banjarsari, Nusawungu, Cilacap go abroad in reason to improve the family economy that their families hopefully become more harmonious. However, after their family economy are fulfilled, dispute in their domestic household often happens, even it causes divorce. This paper explains the basis of normative and juridical causes of the divorce among the migrant workers in Banjarsari, Nusawungu, Cilacap.